Tantangan Hukum Dan Peran Pemerintah Dalam Pembangunan E-Commerce - Rosmayati, Siti (Koaliansi : Cooperative Journal, 2023)
In an era of rapidly developing economies, the dynamics of globalization, free trade, and the development of information and telecommunications technology have shaped a wider and more diverse trade landscape. From locally produced goods and services to those produced overseas, they are available in a wide variety. This innovation also brings telecommunication facilities and sophisticated information technology products that integrate various information media, providing convenience in daily activities.. In this model, sellers and buyers can transact through E-commerce platforms without having to face each other physically. Electronic-based commerce, both now and in the future, has the potential for a broad market share and is capable of becoming an important pillar in the structure of the national economy. Statistical data on the development of E-commerce shows an increase every year, even though this penetration has penetrated the small and medium scale business sector.